PENINGKATAN HASIL BELAJAR PAI MATERI ZIKIR DENGAN DEMONSTRASI MENYANYI DAN ALAT PERAGA TIANG PINTAR - Lestari (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve student learning outcomes in Islamic Religious Education Subjects in recitation material by using the singing demonstration method and the use of PAI smart pole props in class III-1 of 004 ​​North Balikpapan Public Elementary School in North Semester 2016/2017 Academic Year. The problem in this study is how to improve student learning outcomes in the material of recitation. The method used in this research is Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of four stages, namely: planning, acting, observing, and reflecting. The results of the study showed that there was an increase in learning outcomes of Islamic Religious Education Subjects in recitation material using singing demonstrations and PAI smart pole props namely: the number of completeness in the pre-cycle was only 10 people (32.2%) increased to 20 complete people (64.5 %) in the first cycle and increased to 27 students (87.09%) in the second cycle. The research concludes that the singing demonstration and PAI smart pole props can improve student learning outcomes in class III-1 of 004 ​​North Balikpapan Public Elementary School, even semester, 2016/2017 academic year.